Barriers and Enablers of Water Conservation in Formal Residential Households in Cape Town, South Africa - Kassam, Zain (Department of Environmental and Geographical Science, 2021)
In recent years, climate change has caused great changes in weather patterns such as extreme changes in rainfall leading to prolonged drought. Rapid urbanization has led to more than half of the world's population living in urban centres, and the growing urban population must share increasing scarcity of water, exacerbated by climate change. Thus, climate change and urbanization has contributed to the emergence of more water-stressed cities. This thesis is concerned with water conservation as a method of adaptation to an urban water crisis. It looks into the water crisis in the City of Cape Town that took place during 2015-2017. The severe water crisis has been attributed to prolonged drought, rapid population growth, reliance on six-rain-fed dams to provide 95% of the city's water supply, and excessively high water use by formal residential households. The City of Cape Town took various measures to manage both the demand and the supply of water in order to alleviate the stress caused by the water scarcity. From January 2016, a public education campaign was paired with progressively increased water restrictions. However, despite the growing water restrictions and the worsening of the water crisis, Capetonians did not reduce water consumption enough. Against this background, this thesis aims at gaining a nuanced understanding of the barriers and enablers to water conservation amongst residents in formal residential households in the City of Cape Town. The study focuses on formal residential households because the residents use 65% of the total municipal water supply. Data collection was carried out primarily in the Southern and Northern suburbs and consisted of in-depth interviews with 44 respondents using a semi-structured interview guide about daily water conservation as well as perceptions of the water crisis and of their role in mitigating the water crisis. The data analysis involved development of a coding system and identification of three categories of water savers amongst the highest, the lowest, and the median levels of water conversation within the data set, referred to as respective the ‘avid', the ‘low' and the ‘moderate' water savers. The key findings are that the main barrier of water conservation for the ‘low water savers' is lack of willingness to inconvenience one-self in relation to water conservation. Other important barriers to water conservation for the ‘low water savers' included lack of information regarding the on-going water crisis, perceptions of the water crisis as non-urgent, limited trust in water governance institutions, and interest in maximising own benefit from the common water resource. The dominant enabler amongst the ‘avid water savers' is the pro-environment identity they possess, combined with a high self-efficacy to make a difference to the water crisis through their actions. The study showed that this dominant enabling factor works as a catalyst to enhance other enabling factors, especially seeking information and engaging in conversations about water conservation within their social networks. Barriers such as the discomfort of taking short showers, standing inside a bucket during a shower and collecting greywater for re-use are seen as necessary actions that align with their identity and altruistic outlook towards the environment. Interestingly, ‘the moderate water savers' held similar proenvironment identity but were constrained, mostly by institutional barriers, to reduce their water use. Thus, the overall argument is that there is not one barrier or one enabler to water conservation. Rather, the main argument is that an overriding enabling factor for increased water conservation in daily life is a pro-environment identity combined with a high sense of self-efficacy. Finally, this study has shown that the factor of Personal Characteristics, serves as the main enabler and as the main barrier to water conservation because Personal Characteristics have a ripple effect on how factors such as Information, Social, Technical, Financial or Institutional factors affect a respondent's water conservation.